Psychological Inflexibility and Non-Suicidal Self-Injury (NSSI) Behavior among Emerging Adults: Life Satisfaction as Moderator - Khairunnisa, Nadira; Oriza, Imelda Ika Dian (Analitika: Jurnal Magister Psikologi UMA, 2023)
This study aims to examine the role of life satisfaction level as a moderator in the correlation between psychological inflexibility and NSSI behavior. Self-harm behavior without any intention to commit suicide (non-suicidal self-injury (NSSI)) is now widely practiced by adolescents and young adults. Participants in this study were 224 participants aged 18-29 years (average age 22.21 years, 81.3% female). Life satisfaction levels were measured using the Satisfaction with Life Scale (SWLS), psychological inflexibility was measured using the Acceptance and Action Questionnaire-II (AAQ-II), and NSSI behavior was measured using the Non-Suicidal Self-Injury Function Scale (NSSI-FS). Moderation analysis was done using Hayes 4.0. The results of the moderation analysis show that level of life satisfaction significantly moderates the relationship between psychological inflexibility and NSSI behavior. This is consistent with the research hypothesis, namely the level of life satisfaction can weaken the relationship between psychological inflexibility and NSSI behavior. Therefore it can be concluded that individuals can weaken the effects of psychological inflexibility by increasing their life satisfaction.